Peran Gender dalam Perekonomian Rumah Tangga Petani pada Masyarakat Adat - Nugrahayuningtyas, Alifa; Wahyuni, Ekawati Sri (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
Ethnic communities in Indonesia mostly live in rural areas by making use of natural resources and agriculture as the main livelihood. The typical ordinance determines the gender division of labour carried out ethnic communities on the farming system. One of the ethnic communities in Central Java who live in rural areas and make use of natural resources for agricultural activity is community Samin. The purpose of this research, in general, is to analyzing the pattern of the division of gender roles in the household economy of the farmers in the indigenous communities. The research uses quantitative methods supported by qualitative methods. The research shows the principle of the sareng-sareng (together) is used on the farmer households in sedulur sikep. Division of labor in farmers houseolds of communities sedulur sikep is more flexible compared to the division of labor in farmers household of non sedulur sikep because work is done mostly in agriculture that makes it easy to switch roles in the division of laborKeywords: Ethnic communities, farming households, genderÂ ABSTRAK Komunitas etnis di Indonesia sebagian besar hidup di daerah pedesaan dengan memanfaatkan sumberdaya alam dan menjadikan pertanian sebagai mata pencaharian utama. Tata cara yang khas menentukan pembagian kerja gender yang dilakukan komunitas etnis pada sistem pertanian. Salah satu komunitas etnis di Jawa Tengah yang hidup di pedesaan serta memanfaatkan sumberdaya alam untuk aktivitas pertanian adalah komunitas Samin. Tujuan penelitian ini secara umum yaitu menganalisis pola pembagian peran gender dalam perekonomian rumah tangga petani di masyarakat adat. Penelitian dilakukan dengan metode kuantitatif didukung dengan metode kualitatif. Hasil penelitian menunjukkan bahwa prinsip sareng-sareng (bersama-sama) digunakan pada rumah tangga petani di sedulur sikep. Pekerjaan yang dilakukan sedulur sikep sebagian besar di bidang pertanian memudahkan untuk penggantian peran dalam pembagian kerja sehingga pembagian kerja rumah tangga petani di komunitas sedulur sikepÂ lebih fleksibel dibandingkan dengan pembagian kerja rumah tangga petani di non sedulur sikep.Kata Kunci : Gender, komunitas etnis, rumah tangga petani